Two Hits for Bone Regeneration in Aged Patients: Vertebral Bone Marrow Clot as a Biological Scaffold and Powerful Source of Mesenchymal Stem Cells - Salamanna, Francesca; Contartese, Deyanira; Borsari, Veronica; Pagani, Stefania; Barbanti Brodano, Giovanni; Griffoni, Cristiana; Ricci, Alessandro; Gasbarrini, Alessandro; Fini, Milena (Frontiers in Bioengineering and Biotechnology, 2022)
Recently, the use of a new formulation of bone marrow aspirate (BMA), the BMA clot, has been described. This product entails a naturally formed clot from the harvested bone marrow, which retains all the BMA components preserved in a matrix biologically molded by the clot. Even though its beneficial effects were demonstrated by some studies, the impact of aging and aging-associated processes on biological properties and the effect of BMA cell-based therapy are currently unknown. The purpose of our study was to compare selected parameters and properties of clotted BMA and BMA-derived mesenchymal stem cells (MSCs) from younger (<45 years) and older (>65 years) female donors. Clotted BMA growth factors (GFs) expression, MSCs morphology and viability, doubling time, surface marker expression, clonogenic potential, three-lineage differentiation, senescence-associated factors, and Klotho synthesis from younger and older donors were analyzed. Results indicated that donor age does not affect tissue-specific BMA clot regenerative properties such as GFs expression and MSCs morphology, viability, doubling time, surface antigens expression, colony-forming units, osteogenic and adipogenic differentiation, and Klotho and senescence-associated gene expression. Only few differences, i.e., increased platelet-derived growth factor-AB (PDGF-AB) synthesis and MSCs Aggrecan (ACAN) expression, were detected in younger donors in comparison with older ones. However, these differences do not interfere with all the other BMA clot biological properties. These results demonstrated that BMA clot can be applied easily, without any sample processing and avoiding potential contamination risks as well as losing cell viability, proliferation, and differentiation ability, for autologous transplantation in aged patients. The vertebral BMA clot showed two successful hits since it works as a biological scaffold and as a powerful source of mesenchymal stem cells, thus representing a novel and advanced therapeutic alternative for the treatment of orthopedic injuries.